A Two-Week Insulin Infusion in Intrauterine Growth Restricted Fetal Sheep at 75% Gestation Increases Skeletal Myoblast Replication but Did Not Restore Muscle Mass or Increase Fiber Number - Chang, Eileen I.; Hetrick, Byron; Wesolowski, Stephanie R.; McCurdy, Carrie E.; Rozance, Paul J.; Brown, Laura D. (Frontiers in Endocrinology, 2021)
Intrauterine growth restricted (IUGR) fetuses are born with lower skeletal muscle mass, fewer proliferating myoblasts, and fewer myofibers compared to normally growing fetuses. Plasma concentrations of insulin, a myogenic growth factor, are lower in IUGR fetuses. We hypothesized that a two-week insulin infusion at 75% gestation would increase myoblast proliferation and fiber number in IUGR fetal sheep. Catheterized control fetuses received saline (CON-S, n=6), and the IUGR fetuses received either saline (IUGR-S, n=7) or insulin (IUGR-I, 0.014±0.001 units/kg/hr, n=11) for 14 days. Fetal arterial blood gases and plasma amino acid levels were measured. Fetal skeletal muscles (biceps femoris, BF; and flexor digitorum superficialis, FDS) and pancreases were collected at necropsy (126±2 dGA) for immunochemistry analysis, real-time qPCR, or flow cytometry. Insulin concentrations in IUGR-I and IUGR-S were lower vs. CON (P≤0.05, group). Fetal arterial PO2, O2 content, and glucose concentrations were lower in IUGR-I vs. CON (P≤0.01) throughout the infusion period. IGF-1 concentrations tended to be higher in IUGR-I vs. IUGR-S (P=0.06), but both were lower vs. CON (P≤0.0001, group). More myoblasts were in S/G2 cell cycle stage in IUGR-I vs. both IUGR-S and CON (145% and 113%, respectively, P≤0.01). IUGR-I FDS muscle weighed 40% less and had 40% lower fiber number vs. CON (P≤0.05) but were not different from IUGR-S. Myonuclear number per fiber and the mRNA expression levels of muscle regulatory factors were not different between groups. While the pancreatic β-cell mass was lower in both IUGR-I and IUGR-S compared to CON, the IUGR groups were not different from each other indicating that feedback inhibition by endogenous insulin did not reduce β-cell mass. A two-week insulin infusion at 75% gestation promoted myoblast proliferation in the IUGR fetus but did not increase fiber or myonuclear number. Myoblasts in the IUGR fetus retain the capacity to proliferate in response to mitogenic stimuli, but intrinsic defects in the fetal myoblast by 75% gestation may limit the capacity to restore fiber number.